Application of Interpolation Algorithm in Data Processing of the Advanced Multi-electrode Electrical Sounding Method to Determine Saturation Line in the Earth Dam - Minh, Vu Duc (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: Improving the efficiency of data processing of the Advanced Multi-electrode Electrical Sounding method is a practical work and necessary. Previously, we have used the Advanced Multi-electrode Electrical Sounding method to locate saturation line in the earth dam with the positive results. However, one of the data processing steps only stopped at Trendline method, hence the difference to the results measured by the Pizomet systems is good but a lot to be desired. In this paper, we present several new results determining the saturation line of earth dam in Dong Mo, Ha Noi by the Advanced Multi-electrode Electrical Sounding method using the interpolation method and the second derivative during data processing. The results are more accurate than the previous results, with the biggest error of 5.1% compared to the results determined by Pizomet system. Keywords: Trendline, interpolation method, second derivative, Polyfit, error.